2020
DOI: 10.14710/kapal.v17i2.27892
|View full text |Cite
|
Sign up to set email alerts
|

Sloshing Simulation of Single-Phase and Two-Phase SPH using DualSPHysics

Abstract: The sloshing phenomenon is one of the free surface flow that can endanger liquid cargo carriers such as ships. Sloshing is defined as the resonance of fluid inside a tank caused by external oscillation. When sloshing is close to the natural frequency of the tank it could endanger ships. Particle method has the advantages to be applied because sloshing is dealing with free surface. One of the particle methods is Smoothed Particle Hydrodynamics (SPH). In this study, compressible SPH was used as a result of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…Most researchers use the SPH method in analyzing nonlinear free-surface flow problems and the interactions on solid structures. Such as research on breaking wave modelling and the interaction of coastal structures with water waves [3,4], sloshing in the prismatic tank [5][6][7][8], and the impact of water waves on offshore structures [9]. These studies showed the potential of using SPH method in marine and coastal engineering applications and application for actual problem in engineering field.…”
Section: Introductionmentioning
confidence: 94%
“…Most researchers use the SPH method in analyzing nonlinear free-surface flow problems and the interactions on solid structures. Such as research on breaking wave modelling and the interaction of coastal structures with water waves [3,4], sloshing in the prismatic tank [5][6][7][8], and the impact of water waves on offshore structures [9]. These studies showed the potential of using SPH method in marine and coastal engineering applications and application for actual problem in engineering field.…”
Section: Introductionmentioning
confidence: 94%
“…SPH is a meshless and Lagrangian approach suitable for large deformation problems such as water wave propagation, sloshing, and dam break, and related studies. Application for free surface flow, such as sloshing, was performed for a prismatic tank with and without baffle [1][2][3][4]. The results indicate SPH has good accuracy for violent flow in the sloshing phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…Sloshing inside a ship's LNG fuel tank was conducted in 3 hours duration in real-time and could provide reasonable local pressure estimations [5]. Multi-phase flow sloshing was performed with δ-SPH and particle shifting technique [6], and a similar study was conducted with a prismatic tank for two and three dimensions of twophase SPH [7,8]. The results showed SPH has good agreement with both quantitative and qualitative, though in three-dimension computation takes time to compare with mesh-based CFD solver.…”
Section: Introductionmentioning
confidence: 99%